Effects of cultivar, irrigation interval and nitrogen on seed yield, oil content and quality of sunflower (Helianthus annuus L.) - fadlalmola, meera; Abd Elrahman, Hashim; Mohamed, Ibrahim; El- Tayeb, El Tohami; Gangi, Ali (Gezira Journal of Agricultural Science; Vol 12 No 2 (2014), 2014)
Field trials were carried out during summer (2010/11) and winter (2011/12) seasons. The objective of the study was to investigate the effects of two sunflower cultivars: Hysun33 (hybrid) and Damazin-1 (open-pollinated), three irrigation intervals: (7, 14 and 21 days) and three rates of nitrogen in the form of urea: (0, 86 and 129 kg N/ha) on seed yield, oil content and quality of sunflower. Hysun33 significantly out-performed Damazin-1 in seed yield, oil content and quality during the winter season, while Damazin-1 had a higher seed yield, higher oil content and quality compared with Hysun 33 during the summer season. The 7-day irrigation interval gave the highest seed yield compared with 14 and 21-day irrigation intervals during the summer season. However, the 14-day irrigation interval out-yielded the two other irrigation intervals during the winter season. The highest oil content was obtained by both cultivars (Hysun33 and Damazin-1) in both seasons with 7-day irrigation interval. Nitrogen rate of 129 kg/ha gave the highest seed yield (1.56 and 1.17 t/ha) during the summer season. The highest oil content (39.72% and 35.85%) was obtained when 86 kg N/ha was applied during both seasons. Stearic, palmitic, oleic and linoleic acids were the most dominant fatty acids in sunflower seed oil. Hysun33 significantly out-yielded Damazin-1 in oleic and linoleic acids in both seasons. However, Damazin-1 had significantly higher content of stearic and palmitic acids in both seasons. Based on this study, to obtain high seed yield and high oil content and quality of sunflower, it is recommended to grow Damazin-1 in summer and Hysun33 in winter, irrigate every 14 days and apply 86 kg N/ha for both cultivars.  أجريت التجارب الحقلية خلال العروة الصيفية موسم((11/2010 والشتوية موسم 12/2011)). هدفت الدراسة لمعرفة تأثير صنفي زهرة الشمس: هايصن33 (هجين) ودمازين-1 (مفتوح التلقيح)   وثلاث  فترات ري: (7، 14 و 21يوم) وثلاث معدلات نيتروجين في صورة يوريا: (صفر، 86 و 129كجم N /هكتار) على إنتاجية وكمية ونوعية زيت زهرة الشمس. تفوق الصنف هايصن33 معنوياً علي الصنف دمازين-1 في الإنتاجية وكمية ونوعية الزيت في العروة الشتوية، بينما أعطي الصنف دمازين-1 أعلى إنتاجية وكمية ونوعية زيت مقارنة بالصنف هايصن33 في العروة الصيفية. أعطت فترة الري كل7   –يوم أعلى إنتاجية بذور مقارنة بفترتي الري  و14- 21يوم في العروة الصيفية. تفوقت  فترة الري كل  –14يوم- إنتاجياً-على الفترتين الأخريين في العروة الشتوية.  أعلى كمية زيت تحققت لكلا الصنفين (هايصن33 ودمازين- (1في كلا العروتين عند الري كل  7أيام. حقق معدل النيتروجين ( 129كجم N/هكتار) أعلى إنتاجية بذور خلال العروة الصيفية. تحققت أعلى كمية زيت عند إضافة 86 كجم نيتروجين/هكتارخلال العروتين. أحماض السيتاريك، البالماتيك، الأوليك واللينوليك هي الأحماض الدهنية السائدة في بذرة زهرة الشمس. أظهر الصنف هايصن33 تفوقاً  معنوياً علي الصنف دمازين-1 في أحماض الأوليك واللينوليك في كلا العروتين. بينما أعطى الصنف دمازين-1 أعلى محتوى من أحماض السيتاريك والبالماتيك خلال العروتين. بناءاً على هذه الدراسة للحصول على أعلى إنتاجية وأعلى كمية ونوعية زيت زهرة الشمس يوصى بزراعة الصنف دمازين-1 في العروة الصيفية والصنف هايصن33 في العروة الشتوية والري كل  14يوماً وإضافة 86 كجم نيتروجين/هكتار لكلا الصنفين.